Serotonergic mechanisms of the lateral parabrachial nucleus in renal and hormonal responses to isotonic blood volume expansion - Margatho, Lisandra Oliveira; Giusti-Paiva, Alexandre; Menani, José Vanderlei [UNESP]; Elias, Lucila Leico Kagohara; Vivas, Laura M.; Antunes-Rodrigues, Jose (Amer Physiological Soc, 2007)
This study investigated the involvement of serotonergic mechanisms of the lateral parabrachial nucleus (LPBN) in the control of sodium (Na+) excretion, potassium (K+) excretion, and urinary volume in unanesthetized rats subjected to acute isotonic blood volume expansion (0.15 M NaCl, 2 ml/100 g of body wt over 1 min) or control rats. Plasma oxytocin (OT), vasopressin (VP), and atrial natriuretic peptide (ANP) levels were also determined in the same protocol. Male Wistar rats with stainless steel cannulas implanted bilaterally into the LPBN were used. In rats treated with vehicle in the LPBN, blood volume expansion increased urinary volume, Na+ and K+ excretion, and also plasma ANP and OT. Bilateral injections of serotonergic receptor antagonist methysergide (1 or 4 mu g/200 eta 1) into the LPBN reduced the effects of blood volume expansion on increased Na+ and K+ excretion and urinary volume, while LPBN injections of serotonergic 5-HT2a/HT2c receptor agonist, 2.5-dimetoxi-4-iodoamphetamine hydrobromide (DOI;1 or 5 mu g/200 eta 1) enhanced the effects of blood volume expansion on Na+ and K+ excretion and urinary volume. Methysergide (4 mu g) into the LPBN decreased the effects of blood volume expansion on plasma ANP and OT, while DOI (5 mu g) increased them. The present results suggest the involvement of LPBN serotonergic mechanisms in the regulation of urinary sodium, potassium and water excretion, and hormonal responses to acute isotonic blood volume expansion.
Keywords: serotonin; natriuresis; atrial natriuretic peptide; oxytocin; vasopressin